(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
Liquefied Petroleum Gas (LPG) is widely used for domestic and industrial purposes, but leakage of LPG can lead to serious hazards such as fire accidents and explosions. This project presents the design and implementation of an LPG gas detection system that ensures safety by providing early warning in case of gas leakage. The system uses a gas sensor (such as MQ-2 or MQ-6) to continuously monitor the presence of LPG in the environment. When the gas concentration exceeds a predefined threshold, the sensor sends a signal to the microcontroller, which activates an alarm system, such as a buzzer and LED indicator. Additionally, the system can be enhanced with features like automatic exhaust fan activation or SMS alerts using IoT modules for remote monitoring. The proposed system is cost-effective, reliable, and easy to install, making it suitable for homes, kitchens, and small industries. This project aims to minimize risks associated with LPG leakage and improve safety standards through timely detection and alert mechanisms